Welding fireproof cotton and preparation method thereof

By wrapping a fire-resistant layer composed of multiple materials on the alumina fiber matrix layer, the existing fire-resistant cotton has been solved, and higher fire-resistant performance and high-temperature resistance are achieved.

CN119426767AActive Publication Date: 2025-02-14GUANGDONG KAIDUN NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411890670.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-02-14
Estimated Expiration
2044-12-20

AI Technical Summary

Technical Problem

In the prior art, fire-resistant cotton has problems such as poor fire resistance and urgently improving flame retardant performance.

Method used

Alumina fibers are used as the matrix layer and a fire-retardant layer is wrapped on its surface. The fire-retardant layer is composed of polyester resin, nano-silica, hydroxypropyl cellulose, composite fibers, flame retardant, modified perlite powder, Antioxidants, dispersants, defoamers, leveling agents and water, and the flame retardant is obtained by mixing magnesium hydroxide and phosphorus doped biochar.

Benefits of technology

It significantly improves the flame retardant performance and high temperature resistance of the fire-resistant cotton, extends the fire-proof duration, and enhances the strength and adhesion of the fire-proof layer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005200580590000091
    Figure BDA0005200580590000091
  • Figure BDA0005200580590000101
    Figure BDA0005200580590000101
Patent Text Reader

Abstract

The invention discloses welding fireproof cotton and a preparation method thereof, and belongs to the field of fireproof materials.Magnesium hydroxide and phosphorus-doped biochar are compounded for use, can interact with other base materials to form a good flame-retardant system and have a synergistic effect with an antioxidant to achieve the more remarkable fireproof purpose, and the flame-retardant effect is good. And under the synergistic effect of the modified perlite powder and the composite fibers, the high temperature resistance of the system can be improved. Wherein the phosphorus element with a remarkable flame-retardant effect is doped and introduced into the biochar, high-temperature pyrolysis is performed, the phytic acid and the biochar form a phosphorus-containing carbonized layer which is difficult to burn, the material is optimized in the aspect of the molecular structure, and the fireproof performance of the system can be further improved; besides, phosphorus is also introduced into the modified perlite powder, synergistic flame retardance is achieved, the compatibility of the modified perlite powder in a system can be improved under the action of a silane coupling agent, and a fireproof layer with more excellent uniformity, adhesive force and flame retardance can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fireproof material preparation, and in particular to welding fireproof cotton and a preparation method thereof. Background Art

[0002] In electric welding operations, fire-fighting equipment is rarely used to collect sparks, which leads to certain safety hazards during electric welding. It not only affects the health of welders, but also causes fires in serious cases. Therefore, it is extremely important to develop a safe and effective welding fireproof cotton.

[0003] There are also related fireproof products in the prior art, such as welding blankets, fireproof blankets, etc. These products are mainly made of fireproof and non-combustible fibers, which are processed after special processing. The main characteristics are non-combustible, high temperature resistant (550-1100°C), compact structure, non-irritating, soft and tough texture, and convenient for wrapping objects and equipment with uneven surfaces. Among them, the welding blanket can well protect the object away from the hot fire point and spark area, and completely prevent combustion or isolate combustion. During the welding process, the welding blanket is laid on both sides of the object to avoid contact between the spark and the object or avoid sparks from splashing out. This application uses alumina fiber as the base layer. The long-term use temperature of alumina fiber is 1400°C, and the maximum use temperature can reach 1600°C. Compared with other materials, it has higher refractoriness and has outstanding advantages in fire prevention under high-temperature flames. However, the single alumina fiber layer cannot cope with the impact resistance of the flame, its fire resistance is poor, and the fire resistance time is short, which limits its application, and there is still room for improvement in high-temperature flame retardancy. Summary of the invention

[0004] Based on this, in order to solve the problem that the fireproof cotton in the prior art has poor fire resistance and the flame retardant performance needs to be improved urgently, the present invention provides a welding fireproof cotton and a preparation method thereof, and the specific technical scheme is as follows:

[0005] A welding fireproof cotton, comprising a base layer and a fireproof layer wrapped on the surface of the base layer, and the fireproof layer comprises the following preparation raw materials by weight:

[0006] 35-38 parts of polyester resin, 9-11 parts of nano silicon dioxide, 3-5 parts of hydroxypropyl cellulose, 1-7 parts of composite fiber, 3-9 parts of flame retardant, 3-9 parts of modified perlite powder, 1-5 parts of antioxidant, 1-2 parts of dispersant, 1-2 parts of defoaming agent, 1-3 parts of leveling agent and 10-15 parts of water;

[0007] The flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of (1-3): (1-2).

[0008] Furthermore, the acid value of the polyester resin is a carboxyl polyester resin between 60 mgKOH / g and 80 mgKOH / g.

[0009] Furthermore, the composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of (1-5):(1-3):(1-9).

[0010] Furthermore, the preparation method of the modified perlite powder is: heat treating the perlite powder at 250°C to 350°C for 15min to 30min, then cooling to 60°C to 65°C, adding a phosphoric acid solution with a pH of 5.5, stirring for 20min to 30min, then adding a silane coupling agent solution, continuing to stir for 15min to 30min, washing with water, and drying to obtain the modified perlite powder.

[0011] Furthermore, the mass percentage concentration of the phosphoric acid solution is 5% to 15%, and the mass percentage concentration of the silane coupling agent solution is 3% to 10%.

[0012] Furthermore, the preparation method of the phosphorus-doped biochar is: placing the biochar in a phytic acid solution, mixing evenly, and then heat treating it at 250°C to 300°C for 3h to 5h, cooling it to room temperature, and drying it to obtain the phosphorus-doped biochar.

[0013] Furthermore, the mass percentage concentration of the phytic acid solution is 10% to 15%.

[0014] Furthermore, the base layer is an alumina-based fiber layer.

[0015] Furthermore, the antioxidant is at least one of N-benzylamine, phenylenediamine and N,N-diphenyl-p-phenylenediamine.

[0016] In addition, the present invention also provides a method for preparing welding fireproof cotton, the preparation method comprising the following steps:

[0017] Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, dispersant, defoamer, leveling agent and water into a reaction kettle, heat to 65°C to 85°C, and stir at a speed of 200r / min to 300r / min for 30min to 40min, then add flame retardant, modified pearlite powder and antioxidant, stir at a speed of 350r / min to 500r / min for 50min to 60min to obtain slurry;

[0018] The slurry is coated on the surface of the base layer and dried to obtain welding fireproof cotton.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention uses magnesium hydroxide and phosphorus-doped biochar in a compounded form, which can not only interact with other base materials to form a good flame retardant system, but also synergize with antioxidants to achieve a more significant fire prevention purpose, and under the synergistic effect of modified perlite powder, can increase the high temperature resistance of the system.

[0021] 2. The present invention introduces phosphorus, which has a significant flame retardant effect, into biochar, and pyrolyzes it at high temperature. Phytic acid and biochar form a phosphorus-containing carbonized layer that is difficult to burn, and the material is optimized in molecular structure, which can further improve the fire resistance of the system. In addition, phosphorus is also introduced into the modified perlite powder for synergistic flame retardancy, and under the action of a silane coupling agent, its compatibility in the system is increased, which helps to improve its dispersibility and help to obtain a fireproof layer with better uniformity, adhesion and flame retardancy.

[0022] 3. The present invention optimizes the raw materials for preparing the fireproof layer, while ensuring its excellent flame retardant and fireproof performance. By adding composite fibers, it helps to improve its fireproof performance and also helps to improve the strength of the fireproof layer. The overall preparation process is controllable and has strong operability. DETAILED DESCRIPTION

[0023] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0025] A welding fireproof cotton in one embodiment of the present invention comprises a base layer and a fireproof layer wrapped on the surface of the base layer, and the fireproof layer comprises the following preparation raw materials by weight:

[0026] 35-38 parts of polyester resin, 9-11 parts of nano silicon dioxide, 3-5 parts of hydroxypropyl cellulose, 1-7 parts of composite fiber, 3-9 parts of flame retardant, 3-9 parts of modified perlite powder, 1-5 parts of antioxidant, 1-2 parts of dispersant, 1-2 parts of defoaming agent, 1-3 parts of leveling agent and 10-15 parts of water;

[0027] The flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of (1-3): (1-2).

[0028] In one embodiment, the acid value of the polyester resin is a carboxyl polyester resin between 60 mgKOH / g and 80 mgKOH / g.

[0029] In one embodiment, the composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of (1-5):(1-3):(1-9).

[0030] In one embodiment, the single fiber diameter of the composite fiber is 2 μm to 5 μm.

[0031] In one embodiment, the preparation method of the modified perlite powder is: heat treating the perlite powder at 250°C to 350°C for 15min to 30min, then cooling to 60°C to 65°C, adding a phosphoric acid solution with a pH of 5.5, stirring for 20min to 30min, then adding a silane coupling agent solution, continuing to stir for 15min to 30min, washing with water, and drying to obtain the modified perlite powder.

[0032] In one embodiment, the mass percentage concentration of the phosphoric acid solution is 5% to 15%, and the mass percentage concentration of the silane coupling agent solution is 3% to 10%.

[0033] In one of the embodiments, the preparation method of the phosphorus-doped biochar is: placing the biochar in a phytic acid solution, mixing evenly, and then heat treating it at 250°C to 300°C for 3h to 5h, cooling it to room temperature, and drying it to obtain the phosphorus-doped biochar.

[0034] In one embodiment, the mass percentage concentration of the phytic acid solution is 10% to 15%.

[0035] In one embodiment, the biochar is porous biochar with a specific surface area of ​​1500 m 2 / g~2000m 2 / g.

[0036] In one embodiment, the base layer is an alumina-based fiber layer.

[0037] In one embodiment, the antioxidant is at least one of N-benzylamine, phenylenediamine and N,N-diphenyl-p-phenylenediamine.

[0038] In one embodiment, the dispersant is at least one of polyethylene glycol, polyvinyl pyrrolidone and sodium hexametaphosphate.

[0039] In one embodiment, the defoaming agent is at least one of tributyl phosphate, dodecanol, hexadecanol and octyl alcohol.

[0040] In one embodiment, the leveling agent is a silicone leveling agent.

[0041] In addition, the present invention also provides a method for preparing welding fireproof cotton, the preparation method comprising the following steps:

[0042] Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, dispersant, defoamer, leveling agent and water into a reaction kettle, heat to 65°C to 85°C, and stir at a speed of 200r / min to 300r / min for 30min to 40min, then add flame retardant, modified pearlite powder and antioxidant, stir at a speed of 350r / min to 500r / min for 50min to 60min to obtain slurry;

[0043] The slurry is coated on the surface of the base layer and dried to obtain welding fireproof cotton.

[0044] In one embodiment, the coating thickness of the slurry is 1 mm to 3 mm.

[0045] In one embodiment, the drying process is carried out at a temperature of 120° C. to 125° C. and for a time of 1 hour to 3 hours.

[0046] In the above scheme, by optimizing the raw materials for preparing the fireproof layer, while ensuring its use strength, it can significantly achieve flame retardant and fireproof effects.

[0047] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0048] Embodiment 1:

[0049] A welding fireproof cotton, the welding fireproof cotton comprising a base layer and a fireproof layer wrapped on the surface of the base layer, in this embodiment, the base layer is an alumina-based fiber layer; and the fireproof layer comprises the following preparation raw materials by weight:

[0050] 36 parts of polyester resin, 10 parts of nano-silicon dioxide, 4 parts of hydroxypropyl cellulose, 6 parts of composite fiber, 6 parts of flame retardant, 5 parts of modified pearlite powder, 3 parts of N-benzylamine phenylenediamine, 1 part of sodium hexametaphosphate, 1 part of hexadecanol, 2 parts of organic silicon leveling agent and 13 parts of water; wherein the flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of 2:1; the composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of 2:1:3, and the single fiber diameter of the composite fiber is 2μm;

[0051] A method for preparing welding fireproof cotton comprises the following steps:

[0052] The pearlite powder was heat treated at 300° C. for 20 minutes, then cooled to 60° C., a phosphoric acid solution with a mass percentage concentration of 10% was added, and stirred for 25 minutes, and then a silane coupling agent solution with a mass percentage concentration of 5% was added, and the stirring was continued for 15 minutes, and then washed with water and dried to obtain modified pearlite powder;

[0053] The surface area is 1800m 2 / g of biochar is placed in a phytic acid solution with a mass percentage concentration of 12%, mixed evenly, and then heat-treated at 300°C for 3h, cooled to room temperature, and dried to obtain phosphorus-doped biochar;

[0054] Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, sodium hexametaphosphate, hexadecanol, silicone leveling agent and water into a reactor, heat to 70°C, and stir at 200 r / min for 30 min, then add flame retardant, modified pearlite powder and N-benzylamine phenylenediamine, stir at 350 r / min for 60 min to obtain slurry;

[0055] The slurry is coated on the surface of the alumina-based fiber layer with a coating thickness of 3 mm, and is dried at 120° C. for 2 h to obtain welding fireproof cotton.

[0056] Embodiment 2:

[0057] A welding fireproof cotton, the welding fireproof cotton comprising a base layer and a fireproof layer wrapped on the surface of the base layer, in this embodiment, the base layer is an alumina-based fiber layer; and the fireproof layer comprises the following preparation raw materials by weight:

[0058] 38 parts of polyester resin, 11 parts of nano-silicon dioxide, 3 parts of hydroxypropyl cellulose, 7 parts of composite fiber, 5 parts of flame retardant, 7 parts of modified pearlite powder, 2 parts of N-benzylamine phenylenediamine, 1 part of sodium hexametaphosphate, 1 part of tributyl phosphate, 1 part of organic silicon leveling agent and 12 parts of water; wherein the flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of 3:2; the composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of 2:2:3, and the single fiber diameter of the composite fiber is 2μm;

[0059] A method for preparing welding fireproof cotton comprises the following steps:

[0060] The pearlite powder was heat treated at 320° C. for 25 min, then cooled to 65° C., a phosphoric acid solution with a mass percentage concentration of 11% was added, and stirred for 30 min, and then a silane coupling agent solution with a mass percentage concentration of 8% was added, and the stirring was continued for 15 min, and the modified pearlite powder was obtained after washing with water and drying;

[0061] The surface area is 2000m 2 / g of biochar is placed in a phytic acid solution with a mass percentage concentration of 15%, mixed evenly, and then heat-treated at 300°C for 4h, cooled to room temperature, and dried to obtain phosphorus-doped biochar;

[0062] Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, sodium hexametaphosphate, tributyl phosphate, silicone leveling agent and water into a reactor, heat to 75°C, and process at a stirring speed of 300 r / min for 35 minutes, then add flame retardant, modified pearlite powder and N-benzylamine phenylenediamine, and process at a stirring speed of 400 r / min for 55 minutes to obtain slurry;

[0063] The slurry is coated on the surface of the alumina-based fiber layer with a coating thickness of 3 mm, and is dried at 125° C. for 2 hours to obtain welding fireproof cotton.

[0064] Embodiment 3:

[0065] A welding fireproof cotton, the welding fireproof cotton comprising a base layer and a fireproof layer wrapped on the surface of the base layer, in this embodiment, the base layer is an alumina-based fiber layer; and the fireproof layer comprises the following preparation raw materials by weight:

[0066] 37 parts of polyester resin, 10 parts of nano-silicon dioxide, 4 parts of hydroxypropyl cellulose, 5 parts of composite fiber, 8 parts of flame retardant, 4 parts of modified pearlite powder, 1 part of N-benzylamine phenylenediamine, 1 part of sodium hexametaphosphate, 1 part of tributyl phosphate, 1 part of organic silicon leveling agent and 11 parts of water; wherein the flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of 3:1; the composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of 1:1:3, and the single fiber diameter of the composite fiber is 2μm;

[0067] A method for preparing welding fireproof cotton comprises the following steps:

[0068] The pearlite powder was heat treated at 350° C. for 20 minutes, then cooled to 65° C., a phosphoric acid solution with a mass percentage concentration of 12% was added, and stirred for 25 minutes, and then a silane coupling agent solution with a mass percentage concentration of 10% was added, and the stirring was continued for 20 minutes, and then washed with water and dried to obtain modified pearlite powder;

[0069] The surface area is 1900m 2 / g of biochar is placed in a phytic acid solution with a mass percentage concentration of 12%, mixed evenly, and then heat-treated at 280°C for 5h, cooled to room temperature, and dried to obtain phosphorus-doped biochar;

[0070] Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, sodium hexametaphosphate, tributyl phosphate, silicone leveling agent and water into a reactor, heat to 75°C, and process at a stirring speed of 300 r / min for 40 minutes, then add flame retardant, modified pearlite powder and N-benzylamine phenylenediamine, and process at a stirring speed of 400 r / min for 60 minutes to obtain slurry;

[0071] The slurry is coated on the surface of the alumina-based fiber layer with a coating thickness of 3 mm, and is dried at 125° C. for 2 hours to obtain welding fireproof cotton.

[0072] Comparative Example 1:

[0073] The difference between Comparative Example 1 and Example 3 is that in Comparative Example 1, a single magnesium hydroxide is used as a flame retardant, and the rest is the same as Example 3.

[0074] Comparative Example 2:

[0075] The difference between Comparative Example 2 and Example 3 is that in Comparative Example 2, a single phosphorus-doped biochar is used as a flame retardant, and the rest is the same as Example 3.

[0076] Comparative Example 3:

[0077] The difference between Comparative Example 3 and Example 3 is that the flame retardant in Comparative Example 3 is obtained by mixing magnesium hydroxide and biochar in a mass ratio of 3:1, and the rest is the same as Example 3.

[0078] Comparative Example 4:

[0079] The difference between Comparative Example 4 and Example 3 is that no flame retardant is added in Comparative Example 4, and the rest is the same as Example 3.

[0080] Comparative Example 5:

[0081] The difference between Comparative Example 5 and Example 3 is that a single ceramic fiber is used in Comparative Example 5, and the rest is the same as Example 3.

[0082] Comparative Example 6:

[0083] The difference between Comparative Example 6 and Example 3 is that a single glass fiber is used in Comparative Example 6, and the rest is the same as Example 3.

[0084] Comparative Example 7:

[0085] The difference between Comparative Example 7 and Example 3 is that a single aluminum silicate fiber is used in Comparative Example 7, and the rest is the same as Example 3.

[0086] Comparative Example 8:

[0087] The difference between Comparative Example 8 and Example 3 is that no modified perlite powder is added in Comparative Example 8, and the rest is the same as Example 3.

[0088] Comparative Example 9:

[0089] The difference between Comparative Example 9 and Example 3 is that the pearlite powder in Comparative Example 9 is not modified, and the rest is the same as Example 3.

[0090] The samples of Examples 1 to 3 and the comparative samples of Comparative Examples 1 to 9 were subjected to performance tests, wherein the fire resistance test was conducted in accordance with GB / T9978.1-2018 "Fire resistance test method for building components"; wherein the fire resistance duration refers to the product being able to withstand the corresponding fire duration, and the product's back-to-fire surface is not overheated and its integrity is not damaged during the fire. The results are shown in Table 1 below.

[0091] Table 1: Performance test results

[0092]

[0093]

[0094] From the data analysis in Table 1, it can be seen that the present application helps to improve the fire resistance of the system by optimizing the composition of the flame retardant, and the biochar and perlite powder are both processed, and the treated phosphorus element is doped into the biochar, and the phosphorus element is doped into the perlite powder to further improve the high temperature resistance and fire resistance. The added magnesium hydroxide, phosphorus-doped biochar, modified perlite powder and composite fiber have a synergistic effect, so that the fireproof cotton prepared by the formula has more significant fire resistance.

[0095] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0096] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A welding fireproof cotton, characterized in that: The welding fireproof cotton comprises a base layer and a fireproof layer wrapped on the surface of the base layer, and the fireproof layer comprises the following preparation raw materials by weight: 35-38 parts of polyester resin, 9-11 parts of nano silicon dioxide, 3-5 parts of hydroxypropyl cellulose, 1-7 parts of composite fiber, 3-9 parts of flame retardant, 3-9 parts of modified perlite powder, 1-5 parts of antioxidant, 1-2 parts of dispersant, 1-2 parts of defoaming agent, 1-3 parts of leveling agent and 10-15 parts of water; The flame retardant is obtained by mixing magnesium hydroxide and phosphorus-doped biochar in a mass ratio of (1-3): (1-2).

2. The welding fireproof cotton according to claim 1, characterized in that: The acid value of the polyester resin is a carboxyl polyester resin between 60 mgKOH / g and 80 mgKOH / g.

3. The welding fireproof cotton according to claim 1, characterized in that: The composite fiber is obtained by mixing ceramic fiber, glass fiber and aluminum silicate fiber in a mass ratio of (1-5): (1-3): (1-9).

4. The welding fireproof cotton according to claim 1, characterized in that: The preparation method of the modified pearlite powder is as follows: heat-treating the pearlite powder at 250° C. to 350° C. for 15 to 30 minutes, cooling the pearlite powder to 60 to 65° C., adding a phosphoric acid solution with a pH of 5.5, stirring the solution for 20 to 30 minutes, then adding a silane coupling agent solution, stirring the solution for 15 to 30 minutes, washing the solution with water, and drying the solution to obtain the modified pearlite powder.

5. The welding fireproof cotton according to claim 3, characterized in that: The mass percentage concentration of the phosphoric acid solution is 5% to 15%, and the mass percentage concentration of the silane coupling agent solution is 3% to 10%.

6. The welding fireproof cotton according to claim 1, characterized in that: The preparation method of the phosphorus-doped biochar is as follows: placing the biochar in a phytic acid solution, mixing evenly, then heat treating it at 250° C. to 300° C. for 3 h to 5 h, cooling it to room temperature, and drying it to obtain the phosphorus-doped biochar.

7. The welding fireproof cotton according to claim 6, characterized in that: The mass percentage concentration of the phytic acid solution is 10% to 15%.

8. The welding fireproof cotton according to claim 1, characterized in that: The base layer is an aluminum oxide-based fiber layer.

9. The welding fireproof cotton according to claim 1, characterized in that: The antioxidant is at least one of N-benzylamine phenylenediamine and N,N-diphenyl-p-phenylenediamine.

10. A method for preparing welding fireproof cotton, characterized in that: The preparation method is used to prepare the welding fireproof cotton according to any one of claims 1 to 9, and the preparation method comprises the following steps: Add polyester resin, nano-silicon dioxide, hydroxypropyl cellulose, composite fiber, dispersant, defoamer, leveling agent and water into a reaction kettle, heat to 65°C to 85°C, and stir at a speed of 200r / min to 300r / min for 30min to 40min, then add flame retardant, modified pearlite powder and antioxidant, stir at a speed of 350r / min to 500r / min for 50min to 60min to obtain slurry; The slurry is coated on the surface of the base layer and dried to obtain welding fireproof cotton.

Citation Information

Patent Citations

  • A-level fire-protection energy-saving rubber-plastic compound building insulation material and preparation method thereof

    CN102786740A

  • Water-proof, high-strength, weather resistance, flame-retardant and environment-friendly thermal insulation board and preparation method thereof

    CN108358589A

  • Outer wall structure

    JP1988067367A

  • Fire Protective Compositions and Associated Methods

    US20190352515A1

  • Fire spread prevention member and fire spread suppression method

    WO2016167868A1